Adult Education at Biological Field Stations: Building Capacity for Science Learning. Issue 3 (August 2022) - Zarestky, Jill; Vilen, Lauren; Short, Rachel A.; Struminger, Rhonda; Michelle Lawing, A.
An understanding of science concepts is important for living in modern society. Supporting adults' science learning can be particularly challenging because most adults no longer attend formal educational institutions where access and opportunities are facilitated by teachers and school-sponsored programs. Biological field stations (BFSs) are a newly recognized educational venue that hold considerable intrinsic value for adult science education. In this study, we conducted a survey of 223 U.S. BFSs about their nonformal and informal educational outreach programs for adults. Results show BFSs offer a wide variety of science learning programs for adults, focused heavily on experiential learning to engage learners. These experiences promote interactions with the natural environment and are perceived to increase participants' knowledge and skills. This study has implications for how adult educators can better support the professional development of science educators at BFSs and enrich the general public's science learning.